An Analysis of Institutional Support Structures for Livelihood Promotion in Fringe Villages of Kaziranga Tiger Reserve, Assam - Ashraf, Manisha; Badola, Srishti; Borah, Priyanka (Indian Forester, 2021)
This paper examines the sociological and institutional factors responsible for the status of livelihood interventions in the fringe villages of KTR. The study concludes that human and social capital building and addressing the vulnerability context such as impacts of floods and poverty alleviation are important for the success of income generating activities in KTR. It is recommended to have detailed discussions and coordination among institutional players like Government departments, NGOs and social institutions, and an in-depth understanding of past interventions while making decisions about current and future plans.